Macroscopic and microscopic studies of the nests and the stages involved in the nesting process of Centris muralis Burmeister (Hymenoptera: Apidae: Centridini) bee in the adobe walls, in La Rioja, Argentina - Cilla, Gabriela (2012)
Centris (Wagenknechtia) muralis Burmeister is one of the most common bee species distributed in the xeric region of Argentina. This work describes macro-and micromorphological aspects of the nesting architecture and the stages involved in the process of nesting of C. muralis bee, in the adobe walls of Capayán ruins and recent earthen constructions in Udpinango and Villa Castelli, La Rioja, Argentina. In addition, we discuss the possible factors that may explain the high density of nests observed in the adobe walls of Capayán ruins. These constructions are settled in the northern area of the Monte desert. Our analysis showed that the nest cell walls are strengthened and waterproofed probably by the admixture of organic material to the adobe matrix. Light microscopy of thin sections of the vacated cells showed the inner layers of organic material corresponding to the cocoon, and the outer layer of 0.7 mm thick corresponding to the cell walls consisting mainly of silt and clay, fine sand grains in low rate and absence of grains of sand medium and large. The cell wall was not different in its granulometry from that in the adobe brick, thus suggesting that the cell wall was constructed probably by cementing the particles with bee secretion. The scanning micrographs showed that the cell walls and non-nesting zones exhibited abundant clay crystals in the grain distribution. Pollen from Larrea sp. was observed in high proportions in the nest contents of C. muralis in the Capayán adobe walls.